Analisis Desain Pengaduk terhadap Aliran Fluida pada Rancang Bangun Mesin Pencuci Jig di PT UVW - Iman Mujiarto; Wahyu Isti Nugroho; Kaget Wijaya Omar Tadashi; Diana Langgeng Mustikawati (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
PT UVW uses jigs in the vacuum metalizing process that require washing, which is currently done manually, resulting in inefficiency and risks to operators, thus, jig washer machine was created in order to reduce the risk for operators and increasing efficiency, which based on horizontal mixer. This study analyses the effect of agitator design on fluid flow patterns in a jig washing machine to obtain an optimal design. Two agitator design alternatives were developed and tested using Computational Fluid Dynamics (CFD) simulations at rotational speeds of 70, 75, and 100 rpm, followed by prototype fabrication and performance testing. Simulation results show that the second design produces a higher fluid velocity (20.4 m/s) and a more turbulent and uniform flow pattern compared to the first design (1.7 m/s). Field tests confirmed that the second design achieves higher washing effectiveness (97.14%) with reduced water consumption and shorter washing time. The optimally designed agitator washing machine increases productivity by six times compared to manual washing and reduces operator exposure to hazardous chemicals. This study recommends the second agitator design for improving washing efficiency and effectiveness.